Two new species of Euscorpius (Scorpiones: Euscorpiidae) from Bulgaria, Serbia, and Greece - Fet, Victor; Graham, Matthew R.; Webber, Michael M.; Blagoev, Gergin (Zootaxa, 2014)
Two new species of Euscorpius Thorell, 1876 (subgenus Euscorpius s.str.) (Scorpiones: Euscorpiidae) are described based on morphology and the COI DNA barcoding marker: E. deltshevi sp. n. from northern Bulgaria and neighbouring Serbia (formerly reported as E. carpathicus) and E. solegladi sp. n. from southwestern Bulgaria and neighbouring Greece (formerly reported as E. hadzii).